Love on the shelf - Roberts, Sheila (Mira, 2026)
The battle lines are drawn--between a romance-loving bookseller and the shock jock determined to tear happily-ever-afters apart. Alice Willoughby and her mom run HEA Books, a cozy shop devoted to love stories and the people who crave them. Alice is great at matching customers with their perfect happily-ever-after ... she just can't seem to find her own. Enter Parker Black, a disillusioned radio host who's reinvented himself as a romance-bashing shock jock. Bitter from his breakup with a romance author who turned love into a four-letter word, Parker takes aim at the entire genre--and his on-air rants start stirring up trouble for Alice's loyal customers and their partners. He's arrogant, aggravating, and absolutely not book-boyfriend material. Parker's crusade leads to spirited debates and bookstore protests, but when unexpected sparks fly between the two of them Alice begins to wonder if her favorite trope--enemies to lovers--might actually be playing out in real life. Parker may claim romance is a lie ... but is he protesting a little too much?